1986
DOI: 10.1007/bf00025194
|View full text |Cite
|
Sign up to set email alerts
|

A review of the role of ethylene in biochemical control of ripening in tomato fruit

Abstract: The possible ways in which ethylene controls cell wall degradation and colour change are compared with the control of the respiratory rate of ripening tomato fruit . It would appear that the biosynthesis of ethylene is intimately involved with the former change but control of the latter change is much more complex and could be less ethylene dependent than previously thought . Increases in the respiratory rate may either involve extra-mitochondrial decarboxylation and the cyanide-insensitive part of the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…It was reported that respiration climacteric fruits released a large amount of ethylene during their ripening process to increase the respiration intensity of fruit cells, through which, energy metabolism activities become vigorous. The consumption of sugars would be increased, and starch in pulp cells and the cell wall would degrade under the action of cell wall hydrolases, which caused fruit softening, which is consistent in the results of our group's research (Goodenough, 1986).…”
Section: Discussionsupporting
confidence: 90%
“…It was reported that respiration climacteric fruits released a large amount of ethylene during their ripening process to increase the respiration intensity of fruit cells, through which, energy metabolism activities become vigorous. The consumption of sugars would be increased, and starch in pulp cells and the cell wall would degrade under the action of cell wall hydrolases, which caused fruit softening, which is consistent in the results of our group's research (Goodenough, 1986).…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between ET biosynthesis and the induction of the climacteric peak of respiration during fruit ripening, have been investigated in tomato over the past 50 years ( Goodenough, 1986 ; Chaves Soares and Mello-Farias, 2006 ), but the molecular and metabolomic mechanisms involved are still under investigation. In addition to transgenic technology, gene transfer by genome editing methodologies can lead to the integration of the transgene/cisgene, in order to have a more predictable expression ( Cardi and Neal Stewart, 2016 ).…”
Section: Evolution Of Breeding Technologies For Postharvest Qualitymentioning
confidence: 99%
“…Work has been published on the role of C 2 H 4 in the biochemical control of ripening in tomato fruit (Bleecker, 1987;Goodenough, 1986;Gray et al, 1994;Sawamura et al, 1978;Yang, 1987). Ethylene is thought to regulate fruit ripening by coordinating the expression of genes that are responsible for a variety of processes, including enhancement of a rise in the rate of respiration, autocatalytic C 2 H 4 production, chlorophyll degradation, carotenoid synthesis, conversion of starch to sugars, and increased activity of cell wall degrading enzymes (Biggs et al, 1986;Davies and Grierson, 1989;Gray et al, 1994;Maunders et al, 1987).…”
Section: Gene Expression During Tomato Fruit Ripeningmentioning
confidence: 99%